Landscape history and management of the Phoenix Park 1800-1880 - McCullen, John (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2006)
This thesis examines the landscape history and management of the Phoenix Park between 1800 and 1880. Even though the formation of Ireland’s only royal Park (Phoenix Park) commenced in 1662 on the instructions of Charles II and subsequently created by the Duke of Ormonde, its present landscape and infrastructural evolution is inherited from designs and managerial decisions (including expenditure) which were taken from 1800 to 1880. The starting year, 1800, apart from heralding the familiar Act of Union, was quickly followed in 1801 by two events whose influence impacted on the appearance and management of the Park. The first was an official inspection of the Phoenix Park (required by Government) which revealed that much of it was neglected, and the second, was a series of instructions from Lord Lieutenant Hardwicke to the commissioners of the Board of Works (at the time responsible for managing all areas of the Park) which aimed at accountability and control of expenditure, and improving the integrity of subordinate officers. The public areas (as distinct from its ’private’ and institutional areas) of the Phoenix Park in the seventeenth and eighteenth centuries owed their landscape formation and beauty more to landforms and distant views than to internal designed landscapes. Few landscape works were undertaken in the public areas of the Park from 1800 to 1830. However, from 1832 to 1851 unprecedented expenditure was incurred by Woods & Forests, which resulted in major landscape and infrastructural changes and improvements. Valuable insight is afforded into the wide ranging architectural and management skills of Decimus Burton (commissioned by Woods & Forests), and the role of Jacob Owen, the Board of Works Architect, is clarified in relation to drawings and specifications produced by him for gate lodges and other buildings in the Park. Burton’s successful removal of the high stone walls around the official residences and their demesnes, and the creation of sunken fences in their stead, is perhaps the most significant and daring landscape innovation in the Phoenix Park during the period 1832-1851. In 1840 the North Promenade ground was developed in the Park as a public facility, thus making it one of the earliest amenities of this type available to the public. More than two decades later it was turned into the ’People’s Flower Gardens’ and was noted for its novel experimentation with floral displays. The drainage of the Park in 1847 by Josiah Parkes was a major infrastructural development and success, the influence of which impacted positively on the drainage works generally. In contrast to the public areas of the Park, the landscapes of the official demesnes belonging to the lord lieutenant, chief secretary and under-secretary evolved more evenly from the beginning of the study period in 1800. Decimus Button’s and Ninian Niven’s role in the landscape development of the vice regal demesne is clarified as is Richard Turner’s (the famous iron founder) and Ninian Niven’s collaboration on glasshouse construction in the chief secretary’s demesne. All three demesnes, particularly the under-secretary’s, offer a valuable insight into the workings and evolution of the walled garden. The management structure and line of authority for the Phoenix Park at the beginning of the 1800s was a somewhat paradoxical and complex arrangement, which was rationalised in 1833 by Woods & Forests. From 1800 to 1880 five government departments or their agencies managed either the public areas, the private demesnes and / other Park institutions of the Phoenix Park or both. These departments or their agencies (Board of Works, revamped Board of Works [ 1831 ], Woods & Forests, the Quit Rent Office [QRO], the Board of Public Works[GB] and the Board of Public Works [Irl.]), and the personnel involved are examined. Financial stringency was maintained in relation to the public areas of the Park throughout the period from 1800 to 1880, which contrasted sharply with the expenditure on the vice regal lodge and demesne. However, considerable funding was made available for the landscape and infrastructural development of the public areas of the Park during Woods & Forests tenure from 1829 to 1851. A major bias in public spending on London’ s royal parks vis-a-vis the Phoenix Park was revealed in 1861. During the eighteenth century there is a strong military pressure on the Park which is reflected not only by the number of military institutions and fortifications erected but also by the intensive use of the Park for military reviews, manoeuvres, encampments, and artillery practice. The military’s influence wanes in the nineteenth century but is replaced to a lesser degree by a police presence in a more discreet and mutually beneficial way in the 1830s and 1840s through the erection in the Park of a number of police stations and police training facilities. From 1842 Park management began to discriminate against non-recreational activities taking place in the Park, and from 1860 to the end of the study period there is definitive move towards facilitating recreational activities.
Access restricted on volume 2 due to image copyright concerns. Please consult print copy in the Library. Also available in the Library: McCullen, John. An illustrated history of the Phoenix Park : landscape and management to 1880, Dublin : OPW, 2009 ; ISBN 9781406424256.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin